Anti-oxidative effects of 4-hydroxybenzyl alcohol in astrocytes confer protective effects in autocrine and paracrine manners. - Lidan Luo; Seung-Woo Kim; Hye-Kyung Lee; Il-Doo Kim; Hahnbie Lee; Ja-Kyeong Lee (PLoS ONE, 2017)
4-Hydroxybenzyl alcohol (4-HBA) is an important phenolic constituent of Gastrodia elata Blume (GEB), a traditional herbal medicine used in East Asia. Many activities have been reported to underlie the beneficial effects of 4-HBA in the brain, and in particular, its anti-inflammatory, anti-oxidative, and anti-zinc-toxic effects have been implicated in the postischemic brain. Here, the authors investigated the anti-oxidative effect of 4-HBA on astrocytes and sought to identify the underlying molecular mechanisms involved. 4-HBA dose-dependently suppressed H2O2-induced astrocyte cell death. More specifically, pre-incubation of C6 cells (an astrocyte cell line) with 100 μM 4-HBA for 6 hrs increased survival when cells were treated with H2O2 (100 μM, 1 hr) from 54.2±0.7% to 85.9±1.5%. In addition, 4-HBA was found to up-regulate and activate Nrf2, and subsequently, to induce the expressions of several anti-oxidative genes, such as, HO-1, NQO1, and GCLM. Notably, HO-1 was induced by 3.4-fold in 4-HBA-treated C6 cells, and siRNA-mediated HO-1 knockdown demonstrated that Nrf2 activation and HO-1 induction were responsible for the observed cytoprotective effect of 4-HBA. ERK and Akt signaling pathways were activated by 4-HBA in C6 cells, suggesting their involvements in protective effect of 4-HBA. In addition, 4-HBA-conditioned astrocyte culture medium was found to have neuroprotective effects on primary neuronal cultures or fresh C6 cells exposed to oxidative stress, and these effects seemed to be mediated by glial cell line-derived neurotrophic factor (GDNF) and vascular endothelial growth factor (VEGF), which both accumulated in 4-HBA-treated astrocyte culture media. Thus, the 4-HBA-mediated activation of Nrf2 and induction of HO-1 in astrocytes were found to act via autocrine and paracrine mechanisms to confer protective effects. Furthermore, given the pleiotropic effects of 4-HBA with respect to its targeting of various brain cell types and functions, it would appear that 4-HBA has therapeutic potential for the prevention and amelioration of various brain diseases.